1985
DOI: 10.3168/jds.s0022-0302(85)80921-8
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Vomitoxin (Deoxynivalenol)-Contaminated Wheat by Nonlactating Dairy Cows

Abstract: Our objective was to determine if there were serious deleterious effects of wheat naturally contaminated with vomitoxin (deoxynivalenol) on nonlactating dairy cows. Comparisons were between two Quebec spring wheat sources contaminated with Fusarium graminearum in a feeding trial involving 10 nonlactating Holstein dairy cattle offered good quality hay for ad libitum intake supplemented with wheat-oats concentrate (1 kg concentrate/100 kg body weight). Initially, for 3 wk all cows were fed hay plus wheat-oats co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Therefore, the authors supposed the existence of DON in the maize. In agreement with these results, Trenholm et al (1985) noticed that feed intake was slightly reduced when naturally contaminated grain was added to the ration of non lactating cows. However, no clinical symptoms of illness could be observed that might be attributed to the DON concentration of 1.5 up to 6.4 mg/kg.…”
Section: Deoxynivalenolsupporting
confidence: 81%
“…Therefore, the authors supposed the existence of DON in the maize. In agreement with these results, Trenholm et al (1985) noticed that feed intake was slightly reduced when naturally contaminated grain was added to the ration of non lactating cows. However, no clinical symptoms of illness could be observed that might be attributed to the DON concentration of 1.5 up to 6.4 mg/kg.…”
Section: Deoxynivalenolsupporting
confidence: 81%
“…As an example, a decrease in intake and milk production was observed following the administration of 6 to 8 mg DON per kg of concentrate [89,93] whereas no decrease in these two factors was shown after the administration of up to 12 mg DON per kg of concentrate [6,10]. FB1 seems to only have an effect on daily food consumption since the addition of 148 mg of this toxin per kg of feed had no effect on weaned calves [56].…”
Section: Effects Of Mycotoxins On Feed Intake and Performance Of Dairmentioning
confidence: 99%
“…Trenholm et al (1985) recorded a trend towards decreased grain consumption in cows fed a DONcontaminated ration (640 mg/kg in a grain mix). BWs of cows in the current experiment were unaffected by diet.…”
Section: Feed Intake and Changes In Bwmentioning
confidence: 99%
“…Charmley et al (1993) observed that 40 g/L fatcorrected milk tended to exhibit a quadratic response to DON concentration in the diet (0, 600 and 1200 mg/kg of DON in concentrate DM). Trenholm et al (1985) recorded a trend towards decreased grain consumption in cows fed a DON-contaminated ration (640 mg/kg in a grain mix). Korosteleva et al (2007) found that feeds naturally contaminated with Fusarium mycotoxins can affect the metabolic parameters and immunity of dairy cows.…”
Section: Introductionmentioning
confidence: 99%